2009
DOI: 10.1017/s0376892910000160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grazing restrictions on livestock composition and husbandry practices in Madi Valley, Chitwan National Park, Nepal

Abstract: SUMMARYLivestock grazing restrictions are a common practice in the protected areas of developing countries. Understanding the influence of these restrictions on livestock husbandry is critical because local people's livelihoods often depend on access to grazing lands and biodiversity conservation may be affected by grazing activities. Household surveys and government records were used to examine impacts of grazing restrictions on livestock composition and use of available forage resources in the Madi Valley of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
2
17
0
3
Order By: Relevance
“…Our study confirmed that livestock grazing in the BZCF has been gradually restricted since the introduction of ecotourism. This finding is consistent with Gurung et al (2009).…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed that livestock grazing in the BZCF has been gradually restricted since the introduction of ecotourism. This finding is consistent with Gurung et al (2009).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, livestock grazing was prohibited from the multiple-use areas outside the park as ecosystem degradation due to overgrazing had become a major concern (Sharma 1990, Gurung et al 2009). For instance, livestock grazing was prohibited from the multiple-use areas outside the park as ecosystem degradation due to overgrazing had become a major concern (Sharma 1990, Gurung et al 2009).…”
Section: Land Management Regimes In Chitwan Nepalmentioning
confidence: 99%
“…These two land management regimes adjoin each other in space, with the effects of one likely having direct and/or indirect effects on the other. As such, policies that reduce human reliance on local natural resources (e.g., encouraging the use of non-wood fuel sources and improved livestock breeds) and actively managing tiger habitat are urgently needed (Hjortsø et al 2006, Gurung et al 2009, Thornton 2010. Therefore, given projected human population growth and current per-capita resource demands in Chitwan Treue 2006, CBS 2012), protecting tiger habitat will become increasingly difficult over time.…”
Section: Habitat Change Across Different Land Management Regimesmentioning
confidence: 99%
See 2 more Smart Citations